2017
DOI: 10.1111/apt.14293
|View full text |Cite
|
Sign up to set email alerts
|

The body composition profile is associated with response to anti‐TNF therapy in Crohn's disease and may offer an alternative dosing paradigm

Abstract: In this cohort study, body composition profiles did not correlate well with BMI. Myopenia was associated with primary nonresponse with potential implications for dosing and serves as an explanation for pharmacokinetic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 39 publications
2
57
0
Order By: Relevance
“…Our findings build upon an evolving and conflicting body of evidence on the potential negative impact of obesity in patients with IBD, in particular its impact on treatment response to biologics . While obesity has been consistently shown to negatively impact treatment response to anti‐TNF agents in rheumatic diseases, this evidence has been inconsistent in patients with IBD.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our findings build upon an evolving and conflicting body of evidence on the potential negative impact of obesity in patients with IBD, in particular its impact on treatment response to biologics . While obesity has been consistently shown to negatively impact treatment response to anti‐TNF agents in rheumatic diseases, this evidence has been inconsistent in patients with IBD.…”
Section: Discussionmentioning
confidence: 77%
“…Our findings build upon an evolving and conflicting body of evidence on the potential negative impact of obesity in patients with IBD, in particular its impact on treatment response to biologics. [18][19][20] While obesity has been consistently shown to negatively impact treatment response to anti-TNF agents in rheumatic diseases, this evidence has been inconsistent in patients with IBD. In a meta-analysis of 16 studies with 3130 patients with IBD, we observed that obesity does not significantly influence treatment response to anti-TNF agents (odds of failing therapy, 1.20; 95% CI, 0.88-1.64).…”
Section: Discussionmentioning
confidence: 99%
“…FC, as a measure of luminal inflammation in IBD, was negatively associated with ASMI, which is consistent with the known catabolic effects of chronic inflammation [ 18 , 20 , 47 ]. Lean mass is important in patients with IBD, and has been shown to have a bearing on response to therapy, surgical outcomes, and quality of life [ 15 , 18 , 20 , 48 , 49 ]. Grip strength proved to be a simple anthropometric test that was independently and positively associated with ASMI, while also negatively associated with FMI.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al have hypothesised in AP&T that body composition can indeed predict the outcome of anti‐TNF therapy . There are several reasons why this may be the case.…”
mentioning
confidence: 99%